The ethyl acetate fraction of Gynura procumbens sensitizes widr colon cancer cell line against 5-fluorouracil but shows antagonism with cisplatin - Nunuk Aries Nurulita,; Edy Meiyanto,; Sugiyanto,; Eishou Matsuda,; Masashi Kawaichi, (International Journal of Phytomedicine, 2011)
Our recent study has evaluated the ethyl acetate fraction of Gynura procumbens (FEG) as co-chemotherapeutic agent in combination with 5- fluorouracil (5-FU) and cisplatin (CISP) against WiDr colon cancer cells. This study aimed to assess whether FEG produced synergistic effect with 5- FU and CISP and to evaluate its regulation on proliferation, cell cycle, and cell death induction on WiDr colon cancer cells. (3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyltetrazolium bromide) MTT assay was performed to determine the growth inhibitory effect of both single (FEG, 5-FU, or CISP) and combination treatments. FEG (25-500 μg/mL), 5- FU (25-1000 μM) and CISP (5-100 μM) inhibited cells growth in a dose dependent manner and exhibited an IC50 value of 125 μg/mL, 848 M and 43 M, respectively. FEG sensitized WiDr cells that was treated by 5-FU, boosting its therapeutic potential. Conversely when FEG was combined with CISP, it caused antagonism. The antiproliferative effect of single and combination treatment was determined by studying the cell proliferation kinetics using MTT assay. Flowcytometry and (4’,6-diamidino-2- phenylindole) DAPI staining was used to disclose the mechanism of cell cycle arrest and apoptosis. FEG inhibited cell proliferation, induced G1 and S phase arrest and apoptosis. The inhibitory effect was enhanced when FEG was combined with 5-FU, differing from CISP. According to the datas obtained, FEG possess sensitizing properties causes cell cycle arrest and cell death suppose to be apoptosis on WiDr cells. FEG demonstrates a possibility of additive to synergism properties when combined with 5-FU but shows antagonis with CISP.